Cloning, in silico analysis of upstream sequences and tissue and different external conditions mediated expression studies of three homeologs of TaNPF7.2 of wheat (Triticum aestivum) - V, MUHAMMED SHAMNAS; SINGH, AKANKSHA; KUMAR, ANUJ; SINHA, SUBODH KUMAR (The Indian Journal of Agricultural Sciences, 2026)
The present study was carried out during 2020–2021 at ICAR-National Institute for Plant Biotechnology, New Delhi during 2020–2021 to investigate the cis-regulatory elements, transcription factor (TF) binding sites and stress- and development-responsive expression dynamics of TaNPF7.2, a wheat (Triticum aestivum L.) homolog of the AtNRT1.5/ NPF7.3 responsible for root-to-shoot nitrate transport. Promoter regions ( 2 kb) of TaNPF7.2-A, -B, and –D were analyzed to identify cis-regulatory elements and TF-binding sites. A homeolog-specific expression study was conducted at early and later developmental stages (GS19, GS39, GS65) under different treatments in the nitrogen-uptake-efficient genotype, i.e., K9107. Promoter analysis revealed strong homeolog divergenc with TaNPF7.2-A enriched in general stress-responsive STRE motifs, TaNPF7.2-B harbouring higher MYB and DRE content and TaNPF7.2-D uniquely lacking ABREs but exhibiting dense WRKY-, HD-ZIP– and ZF-HD–binding sites. Expression profiling showed that under optimal nitrate, TaNPF7.2-A was the most strongly induced in seminal roots. Salt stress caused widespread transcriptional suppression whereas drought triggered a delayed but strong induction of TaNPF7.2-B. Cadmium stress induced rapid activation of TaNPF7.2-D, consistent with its WRKY-rich promoter element. During later developmental stages, expression remained predominantly root-centric, with shifting homeolog dominance from 7.2-D (GS19) to 7.2- A (GS65). These findings provide insights into understanding of nitrate translocation in wheat and identify promising regulatory nodes for enhancing NUE under both favourable and stress conditions.